E-PARTISIPASI VIRTUAL DALAM SELAMATKAN LINGKUNGAN DI ERA DIGITAL - Kheyene Molekandella Boer (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2019)
Issues about the environment often become the spotlight of the world, ranging from technological developments to a million environmental problems that never end. Now environmental issues are touched by the rapid development of digital technology. This makes a big change for the world of the environment. Ranging from digital conversations to top level or government decision-making to making environmental policies, all references are taken from community activities and participation that often voice their opinions on social media. Communication technology in the context of the environment that is most widely seen is the phenomenon of online petitions or known as